Competencies for Global Mental Health: Developing Training Objectives for a Post-Graduate Fellowship for Psychiatrists. Issue 4 (5th November 2018) - Buzza, Colin; Fiskin, Anna; Campbell, Jorien; Guo, Jennifer; Izenberg, Jacob; Kamholz, Barbara; Hung, Erick; Acharya, Bibhav
Background: Despite an increase in psychiatry trainees' interest in global mental health (GMH), there is a lack of relevant training competencies developed using educational frameworks that incorporate viewpoints from high- and low-income countries. Objective: The aim of this study was to determine competencies for a two-year post-graduate GMH fellowship for psychiatrists utilizing Kern's six-step process as a theoretical framework for curriculum development. Methods: We conducted a targeted needs assessment via key informant interviews with a purposive sample of stakeholders (n = 19), including psychiatry trainees, generalist clinicians, medical directors, psychiatrists, researchers, and GMH educators from high- and low-resource settings in the United States and abroad. We analyzed data using a template method of thematic analysis. Findings: We tabulated learning objectives across 20 domains. Broadly, clinical objectives focused on providing supervision for short-term, evidence-based psychotherapies and on identifying red flags and avoiding harmful medication use among vulnerable populations such as children and the elderly. Non-clinical objectives focused on social determinants of health, education, and clinical supervision as part of capacity-building for non-specialists, engagement in a systems-wide project to improve care, and ethical and equitable partnerships that involve reciprocal and bidirectional education. Several competencies were also relevant for global health work in general. Conclusions: A theory-informed framework for curriculum development and a diverse set of key informants can provide educational objectives that meet the priorities of the trainees and the clinical sites in both low- and high-income settings. Limitations of this study include a small sample size and a focus on clinical needs of specific sites, both of which may affect generalizability. Given the focus on training specialists (psychiatrists), the low-resource sites highlighted the importance of educating and supervising their permanent, generalist clinicians, rather than providing direct, independent patient care.